Glatiramer Acetate, Dimethyl Fumarate, and Monomethyl Fumarate Upregulate the Expression of CCR10 on the Surface of Natural Killer Cells and Enhance Their Chemotaxis and Cytotoxicity - Maghazachi, Azzam A.; Sand, Kristin L.; Al-Jaderi, Zaidoon (Frontiers in Immunology, 2016)
In vitro harnessing of immune cells is the most important advance in the field of cancer immunotherapy. Results shown in the current paper may be used to harness natural killer (NK) cells in vitro. It is observed that drugs used to treat multiple sclerosis such as glatiramer acetate, dimethyl fumarate and monomethyl fumarate up-regulate the expression of chemokines receptor 10 (CCR10) on the surface of human IL-2-activated NK cells. This is corroborated with increased chemotaxis of these cells towards the concentration gradients of the ligands for CCR10, namely CCL27 and CCL28. It is also demonstrated that these three drugs enhance NK cell cytotoxicity against tumor target cells, an activity that is abrogated by prior incubation of the cells with anti-CCR10 antibody. Because CCL27 and CCL28 are secreted by selective tumor types such as malignant melanoma, squamous cell carcinomas and colorectal cancer, respectively, it is hypothesized that activated NK cells may be harnessed in vitro with any of these drugs before utilizing them as a therapeutic modality for cancer.